Democracy by Design: Perspectives for Digitally Assisted, Participatory Upgrades of Society - Helbing, Dirk; Mahajan, Sachit; Fricker, Regula Hänggli; Musso, Andrea; Hausladen, Carina I.; Carissimo, Cesare; Carpentras, Dino; Stockinger, Elisabeth; Argota Sanchez-Vaquerizo, Javier; Yang, Joshua C.; Ballandies, Mark C.; Korecki, Marcin; et al. (Journal of computational science, 2023)
The technological revolution, particularly the availability of more data and more powerful computational tools, has led to the emergence of a new scientific field called “Computational Diplomacy”. Our work tries to define its scope and focuses on a popular subarea of it, namely “Digital Democracy”. In recent years, there has been a surge of interest in using digital technologies to promote more participatory forms of democracy. While there are numerous potential benefits to using digital tools to enhance democracy, significant challenges must be addressed. It is essential to ensure that digital technologies are used in an accessible, equitable, and fair manner rather than reinforcing existing power imbalances. This paper investigates how digital tools can be used to help design more democratic societies by investigating three key research areas: (1) the role of digital technologies for facilitating civic engagement in collective decision-making; (2) the use of digital tools to improve transparency and accountability in governance; and (3) the potential for digital technologies to enable the formation of more inclusive and representative democracies. We argue that more research on how digital technologies can be used to support democracy upgrade is needed. Along these lines, we lay out a research agenda for the future. •We elaborate and advance the concept of “democracy by design”.•We discuss how digital tools can aid in the democratic upgrade of society.•We discuss the risks of misinformation and polarization and the need for cohesion.•We discuss how voting design affects political legitimacy, trust, and transparency.•We outline a framework to bridge dynamic data flows into responsive physical spaces.